The Relationship Between Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty: A Study of Indonesian Consumers - Purnama Asri, Retno Widowati (Universitas Muhammadiyah Yogyakarta, 2011)
This research investigated direct and indirect relationship between brand equity constructs. We employed the costumer-based brand equity of Aaker’s (1991) which incorporated four dimensions of brand equity namely, brand awareness, brand associations, perceived quality and brand loyalty. This present study looked at Indonesia as one of emerging market which becomes a more important market that there are many growth opportunities internationally, and using the teenager frequent consumers of McDonals’s restaurant as subjects. We chose the object of the famous global brand Mc Donald’s restaurant as the biggest companies of fast food restaurant in hospitality industry that implements local adaptations. We implement Structural Equation Modelling with LISREL to examine the hypothesis. Based on our analysis and result, we found that there are direct and indirect relationship among brand equity construct, whereas perceived quality and brand awareness are important variables which affect brand loyalty.